IN VITRO ANTIOXIDANT AND ANTICANCER ACTIVITY OF ULVA LACTUCA L.USING MOLT-3 CELL LINE - CHIDAMBARARAJAN P; KEERTHANA V; PRIYADHARSHINI K; SAKTHIVEL B (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The aim of the present investigation was to determine the in vitro antioxidant and anticancer activity of the ethanol extract of Ulva lactuca L. Methods: The present study was to investigate the antioxidant and anticancer activity of U. lactuca L. The extract of U. lactuca L. was extracted by ethanol and subject to analysis. An in vitro antioxidant activity of the ethanol extract of U. lactuca L. was performed by 1, 1-diphenyl-2-picrylhydrazyl free radical scavenging assay. Simultaneously anticancer activity was also performed using blood cancer (MOLT-3) cell line, and the species showed a strong selective cell proliferation inhibition of the cancer cell line. Results: The scavenging activity was measured and determined to be 78.5%. This might be due to high polyphenolic compounds and flavonoid contents of the extract, which showed maximum growth inhibition of 74.4%. Conclusion: Thus, the study concludes that the constituents of seaweeds can act as potent in treating various diseases and can be used as an alternative for therapeutic treatment.